GLOBAL DEMOCRACY FROM THE PERSPECTIVE OF GOOD GOVERNANCE AND GLOBAL CITIZENSHIP - Hermansyah Hermansyah; Muhamad Subkhan; Asep Sopian; Arik Darojat; Hermansyah (Institut Pendidikan Indonesia, 2026)
The advancement of globalization has transformed the paradigm of democracy from a state-centered concept into a governance framework that involves multiple stakeholders in addressing transnational issues. This transformation requires the strengthening of democracy beyond electoral mechanisms by emphasizing the implementation of good governance principles and the development of global citizenship as the foundation for democratic, inclusive, and sustainable governance. This study aims to analyze global democracy from the perspectives of good governance and global citizenship and to examine the interrelationship among these three concepts in enhancing the quality of democracy in the contemporary global era. The study employs a qualitative approach using a library research method. Data were collected from reference books, national and international scholarly journals, and other relevant academic documents, and were analyzed through content analysis and descriptive-critical analysis. The findings reveal that global democracy has evolved into a paradigm that emphasizes inclusive political participation, transparency, accountability, the rule of law, and multi-stakeholder collaboration in governance. The implementation of good governance principles plays a significant role in improving government effectiveness, strengthening the legitimacy of public institutions, and promoting meaningful public participation. Furthermore, global citizenship contributes to fostering citizens' awareness, responsibility, and engagement in addressing global challenges. The study concludes that the synergy between global democracy, good governance, and global citizenship constitutes a strategic foundation for establishing democratic, responsive, inclusive, and sustainable governance amid the growing complexity of global challenges.